Deprioritized and disrupted: tuberculosis care in the shadow of COVID-19 - Sharma, Sushant (Frontiers in Public Health, 2025)
The COVID-19 pandemic significantly disrupted tuberculosis (TB) care worldwide, undermining years of progress in TB prevention and control. This Perspective offers a comparative analysis of how TB services were affected in a high-income, low-burden country (Canada) versus two low- and middle-income, high-burden countries (India and Nigeria). Drawing on secondary data and global surveillance reports, the article highlights key disruptions across the TB care cascade, including delays in diagnosis, reduced case detection, and the collapse of community-based treatment models like DOTS. In Canada, digital transitions partially mitigated the impact, though access was unequal. In contrast, India and Nigeria faced widespread diagnostic interruptions, compounded by preexisting infrastructure gaps and limited digital access. The comparison reveals how underlying health system strength and digital readiness shaped national responses and recovery trajectories. Crucially, the pandemic exposed policy inertia and the deprioritization of routine infectious disease care in crisis contexts. This article calls for a global rethink of public health preparedness that centers on equity, continuity of essential services, and support for high burden settings. By analyzing divergent country experiences, this Perspective contributes actionable insights for strengthening TB programs and public health systems during future pandemics.